Fluroine-18 fluorodeoxyglucose-positron emission tomography/computer tomography in staging of renal cell carcinoma arising from a native kidney with liver and bone metastasis in a renal transplant patient - Kamaleshwaran, Koramadai; Rangarajan, Bharat; Jose, Raghi; Shinto, Ajit (World Journal of Nuclear Medicine, 2018)
Renal cell carcinoma (RCC) of the native kidney accounts for <5% of all malignancies found in transplant recipients. There have been only a few reported cases comprising of few renal transplant patients with RCC of native kidneys due to the relative rarity of the condition. Fluorine-18 Fluorodeoxyglucose (FDG)-positron emission tomography (PET)/computed tomography (CT) is used in the staging of RCC. Prognosis of metastatic RCC is poor. We report the first case of 55-year-old postrenal transplant recipient diagnosed with RCC of the native kidney with liver and bone metastases imaged using F-18 FDG PET/CT.
Keywords: Fluoride-18 Fluorodeoxyglucose-positron emission tomography/computed tomography; native kidney; renal cell carcinoma; renal transplant